KESIAPAN BUDAYA MELAYU MASYARAKAT PULAU PENAWAR RINDU BELAKANG PADANG KOTA BATAM DALAM MENYAMBUT PERKEMBANGAN PARIWISATA - Dailami; Sukmamedian, Haufi; Abnur, Asman; Hardini, Widi; Budiartha, I Nyoman; Simatupang, Violetta Cherryline (JURNAL MATA PARIWISATA, 2024)
This study aims to analyze the readiness of the Malay culture in the community of Pulau Penawar Rindu in Belakang Padang, Batam City, in facing tourism development. As one of the potential tourist destinations in the Riau Archipelago, Pulau Penawar Rindu boasts a strong Malay cultural heritage, which serves as the primary attraction for visitors. However, tourism development often brings challenges to the preservation of local culture. This research employs a qualitative approach using in-depth interviews and participatory observation to explore the community’s perceptions regarding their readiness to preserve Malay cultural values amidst the social changes caused by tourism. The results indicate that the local community is highly aware of the importance of cultural preservation, but stronger support from the government and tourism stakeholders is needed to manage sustainable tourism development. This study offers recommendations on local cultural preservation strategies that can be implemented to advance tourism without compromising the Malay cultural identity.